Financial Management Challenges and Solutions for Startups in the Post-Pandemic Era - Ana María Hernandez; Luis García; María Perez (International Forum of Researchers and Lecturers, 2024)
The COVID-19 pandemic has presented unique challenges for startups, particularly in the areas of financial management. This research focuses on the financial obstacles faced by startups in the post-pandemic period, including cash flow management, access to funding, and risk mitigation. Through interviews with entrepreneurs and financial experts, the paper highlights effective strategies that startups have adopted to navigate these challenges, such as digital finance tools, crowdfunding, and lean financial management practices. The study concludes by offering a framework for startups to enhance their financial resilience and sustainability in a volatile economic environment.